The effects of the Jenkyns Event on the radiation of Early Jurassic dinoflagellate cysts - Correia, Vânia (2021)
ABSTRACT: This contribution is an overview of the Early Jurassic dinoflagellate cysts of the Lusitanian Basin in Portugal, with particular emphasis on the effects of the Jenkyns Event (Toarcian Oceanic Anoxic Event) on the evolution of this planktonic group. We review and discuss data from 214 samples from six Lower Jurassic successions (upper Sinemurian to upper Toarcian) in the Lusitanian Basin. The late Pliensbachian radiation of dinoflagellate cysts was well recognized in this basin. The pre-Jenkyns Event interval is highly productive, with maximum abundance and species richness values. However, this palaeoenvironmental perturbation severely affected the evolution of this group for the remainder of the Early Jurassic. The prolonged recovery of the dinoflagellates in the Toarcian following the Jenkyns Event is not typical of the northern regions (Arctic and Boreal realms), where new species began to evolve earlier compared with southern European basins.